PI3K/AKT/mTORC1 signalling pathway regulates MMP9 gene activation via transcription factor NF-κB in mammary epithelial cells of dairy cows - Yongjin Mao; Chen Su; Huilin Yang; Xiaocong Ma; Feng Zhao; Bo Qu; Yang Yang; Xiaoming Hou; Bing Zhao; Yingjun Cui (Animal Biotechnology)
Matrix metalloproteinase 9 (MMP9) plays a pivotal role in mammary ductal morphogenesis, angiogenesis and glandular tissue architecture remodeling. However, the molecular mechanism of MMP9 expression in mammary epithelial cells of dairy cows remains unclear. This study aimed to explore the underlying mechanism of MMP9 expression. In this study, to determine whether the PI3K/AKT/mTORC1/NF-κB signalling pathway participates in the regulation of MMP9 expression, we treated mammary epithelial cells with specific pharmacological inhibitors of PI3K (LY294002), mTORC1 (Rapamycin) or NF-κB (Celastrol), respectively. Western blotting results indicated that LY294002, Rapamycin and Celastrol markedly decreased MMP9 expression and P65 nuclear translocation. Furthermore, we found that NF-κB (P65) overexpression resulted in elevated expression of MMP9 protein and activation of MMP9 promoter. In addition, we observed that Celastrol markedly decreases P65-overexpression-induced MMP9 promoter activity. Moreover, the results of the promoter assay indicated that the core regulation sequence for MMP9 promoter activation may be located at −420 ∼ −80 bp downstream from the transcription start site. These observations indicated that the PI3K/AKT/mTORC1 signalling pathway is involved in MMP9 expression by regulating MMP9 promoter activity via NF-κB in the mammary epithelial cells of dairy cows.